Uncertainty as a regular feature of modern Ukrainian society - Yereskova, Tetyana V. (Teorija in praksa, 2020)
The purpose of this article is to substantiate the pattern of societal uncertainty as being a determinant of collective social behaviour exemplified by Ukrainians' developing societal expectations and perceptions. The results of the "Social Conflictogenity of Ukrainian Society" research project are interpreted with respect to attitudes to the state of "societal uncertainty". A certain destructuring of modern Ukrainian society is shown to be adding to the consolidation of societal uncertainty among members of society as a particular model of interaction among social subjects. It demonstrates that members of Ukrainian society are unwilling to reduce the state of societal uncertainty
Keywords: destrukturiranje družbe; Družba tveganja; družbena negotovost; družbena pričakovanja; družbene perspektive; družbeno restrukturiranje; Negotovost; Risk society; Uncertainty; vpliv